Phenotypic characterization of native pig in Romblon province, Philippines - Falculan, Ken N (Technium BioChemMed, 2021)
This study was conducted to determine the phenotypic characteristics of native pigs in the province of Romblon. Specifically, it identifies the phenotypic characteristics, morphometric diversity, and effective population size of the native pigs. This study used the descriptive design. The data gathered were statistically analysed using frequency/percentage, mean, regression analysis and correlation. From the analysis and interpretation conducted it was found out that: majority of the snout were long and thin; the head profile was straight; most of the ear type was droopy; the ear orientation were projected forward; have straight hair; the coat color pattern were plain; the coat color was black; the skin were smooth; the tail were straight and the backline was straight except for gilt which is swaybacked. The Shannon Weiner Diversity Index on the phenotypic characteristics of native pigs in the province of Romblon was observed evenly distributed. There is significant relationship observe on the morphometric diversity of native pigs.